2017
DOI: 10.1002/aoc.4165
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced adsorption performance of a novel Fe‐Mn‐Zr metal oxide nanocomposite adsorbent for anionic dyes from binary dye mix: Response surface optimization and neural network modeling

Abstract: A novel adsorbent, Fe‐Mn‐Zr metal oxide nanocomposite was synthesized and investigated for removal of methyl orange (MO) and eosin yellow (EY) dyes from binary dye solution. The magnetic nanocomposite has shown surface area of 143.01 m2/g and saturation magnetization of 15.29 emu/g. Optimization was carried out via response surface methodology (RSM) for optimizing process variables, and optimum dye removal of 99.26% and 99.55% were obtained for MO and EY dye, respectively with contact time 62 min, adsorbent do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(14 citation statements)
references
References 52 publications
0
14
0
Order By: Relevance
“…[17][18][19] Due to the strong affinity between chromium and iron, and excellent magnetic property of the iron-based material, different types of iron-based materials have been studied and used as adsorbents for removal of Cr(VI). [20][21][22][23] For example, Hu and co-workers reported an effective adsorbent of jacobsite (MnFe 2 O 4 ) to remove Cr(VI) from wastewater. 24 In fact, a Fe-Mn binary oxide may contain strong oxidation property (manganese dioxide), high adsorption property (iron oxides), and excellent separating property (magnetic materials).…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19] Due to the strong affinity between chromium and iron, and excellent magnetic property of the iron-based material, different types of iron-based materials have been studied and used as adsorbents for removal of Cr(VI). [20][21][22][23] For example, Hu and co-workers reported an effective adsorbent of jacobsite (MnFe 2 O 4 ) to remove Cr(VI) from wastewater. 24 In fact, a Fe-Mn binary oxide may contain strong oxidation property (manganese dioxide), high adsorption property (iron oxides), and excellent separating property (magnetic materials).…”
Section: Introductionmentioning
confidence: 99%
“…It belongs to the spinel group and forms tetragonal crystals. The wide range of technological applications of Mn 3 O 4 depends on its advantages as reported in [8][9][10][11][12][13][14][15][16][17]: (i) it is one of the most stable oxides of manganese. (ii) It is active catalyst for various catalytic reactions such as the decomposition of NO x , drinking water treatment process and the oxidation of both C 6 H 6 and CO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…(v) The separate application of hausmannite nanoparticle is reported for dye remediation by adsorption or photocatalytic degradation. Hausmannite nanoparticles have been synthesized by various methods [12][13][14][15][16][17][18][19][20][21][22][23]. Overall, the synthesis mechanism of Mn 3 O 4 can be divided into two main categories.…”
Section: Introductionmentioning
confidence: 99%
“…Yu et al, 2017 has reported significant dye uptake capacity (103.46 mg/g) of mesoporous ZrO 2 fibers for the removal of congo red dye. However Singh et al, 2017 has investigated the adsorption capability of Fe‐Mn‐Zr trimetal oxide nanocomposite and reported enhanced adsorption capacities of 196.07 mg/g and 175.43 mg/g for MO and eosin yellow dye, respectively as compared to single iron oxide and zirconium oxide nanoparticles. Thanh et al ., 2016 reported a nanoscale Al‐Ti‐Mn trimetal oxide adsorbent combining the oxidation property of manganese dioxide and the high capacity of aluminium oxide and titanium oxide to adsorb arsenic.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al ., 2011 has reported the synthesis of mixed oxides containing Ti and Si (11.89 nm average size) and Ti, Al and Si (12.78 nm average size) with high adsorption capacity of 162.96 mg/g and 65.78 mg/g, respectively, for the adsorptive removal of methylene blue dye which are comparatively higher than the adsorptive capacity of single metal oxide nanoparticles. This improvement in performance of mixed oxides as compared to single metal oxides is due to the synergistic effects between the metals in heterogeneous mixed oxides . To the best of our knowledge, although the characteristics of dye adsorption by single‐component Ca, Fe or Zr oxides have been investigated, the adsorption behavior of the CaFe 2 O 4 and ZrO 2 nanocomposite not yet explored properly.…”
Section: Introductionmentioning
confidence: 99%